Investigating the Health Information Literacy Knowledge of Health Care Students as an Essential Next Step in Medical and Health Professional Training (International Journal of Nursing Education, 2020)
Health information literacy, the ability for individuals to access, evaluate and understand health information successfully and use it to make decisions regarding their health, is a growing subject of research. Widespread access to information particularly via the World Wide Web, has provided information seekers with unprecedented access to resources, however, there is also the potential for access to invalid material. This can especially be problematic for people who find and utilize harmful medical materials. In the medical field, there has been a marked shift toward evidence-based practice (EBP), meaning using valid evidence and reviewing the existing research to ensure that best practices are being incorporated and followed. Health information literacy has been described as a cornerstone and prerequisite to EBP. Healthcare practitioners with these skill sets should be better prepared to make clinical decisions and also guide patients to the best resources they need to understand their health condition. As such, health information literacy should be valuated and included in prospective health care professionals’ training.